French Linguistic Policy in Algeria and its Post-Colonial Dimensions: A study in Linguistic Ecology and Linguistic Imperialism - Zighem, Yamina (Anaquel de Estudios Árabes, 2021)
Language is a value,  growing and developing parallel to time changes. It is revitalized due to factors that are usually natural in order to not be characterized by backwardness and extinction features. However,  it may be exposed to abnormal factors such as colonialism that may lead to a change in the language ecology. During French colonialism, Algeria was experiencing this change in its linguistic environment. They were adoptinga language policy and planning in order to achieve the colonial policyobjectives, and which intentionally affected the course of post-independence language policy and the crystallisation of an (artificial) linguistic environment. So, does an imperialist linguistic policy have the ability to form and create a linguistic environment for Colonial societies? And does it have the ability to control its linguistic future?
Keywords: Linguistic policy; language planning; French colonialism in Algeria; Ecology of language; Linguistic imperialism